2019
DOI: 10.1504/ijhtm.2019.104933
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder identification and salience in purchasing: an empirical study from UK hospitals

Abstract: The lack of systematic processes for stakeholder identification and the omission of key stakeholders in UK hospitals cause significant delays in purchasing processes. This is reinforced by the strict tender processes that follow in making their purchases as a matter of assurance of fairness and competition. This paper presents a descriptive analysis of decision-making processes when the public hospitals purchase diagnostic equipment, and it discovers how the hospitals use stakeholder identification and salienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…However, the findings could support future cross-Trust studies or surveys designed to understand patterns across Trusts. One study by Madhlambudzi and Papanagnou (2019) which also focused on describing and analysing purchasing behaviour specific to diagnostic equipment identified similar lack of stakeholder engagement as a key driver for conflicts and delays in procurement processes [ 25 ], demonstrating the potential for transferability of some of our results (at least, specifically to other NHS settings).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the findings could support future cross-Trust studies or surveys designed to understand patterns across Trusts. One study by Madhlambudzi and Papanagnou (2019) which also focused on describing and analysing purchasing behaviour specific to diagnostic equipment identified similar lack of stakeholder engagement as a key driver for conflicts and delays in procurement processes [ 25 ], demonstrating the potential for transferability of some of our results (at least, specifically to other NHS settings).…”
Section: Discussionmentioning
confidence: 80%
“…Lack of engagement and ‘silo working’ between different cadres of staff involved in procurement from central Trust administration to end users is a recurring theme in hospital procurement literature, with several qualitative and mixed-methods studies noting the absence of mechanisms for connecting stakeholders in procurement [ 23 , 24 ]. One study by Madhlambudzi and Papanagnou (2019) conducted in two other NHS Trusts on diagnostics purchasing noted that there was no deliberate effort to identify and engage key stakeholders when the purchasing decisions is made [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[27] Madhlambudzi & Papanagnou(2019) studied the involvement and salience of several stakeholders in purchasing of diagnostic equipment and found that hospitals fail to identify key stakeholders resulting in possible delays and conflicts. [37] Haas et al ( 2017) concluded that a hospital committee resulted in lower purchasing prices than when physicians selected vendors directly in a study of the selection of prosthetic implants. [28] However, committees are not flawless; Licona et al ( 2009) described a case study to demonstrate involvement of an interdisciplinary network of professionals in health technology management: despite the involved network several anomalies were identified such as uncertainty of who would install equipment after a bidding process.…”
Section: Key Findings From Studiesmentioning
confidence: 99%
“…[10] Empirical studies of purchasers in UK hospitals have shown that there are a wide range of stakeholders potentially involved in purchasing decisions (from clinicians, nurses, biomedical engineers, finance staff and/or managers), but their responsibilities and protocols are ill-defined, their skills and expertise differ, [11] they often work in silos and make decisions under high pressure conditions, [12] and that the lack of stakeholder analysis as part of purchasing planning processes resulted in conflicts and delays in decisions. [13] A more recent scoping literature review of the logistics function in hospitals demonstrated that logistics functions can be highly inefficient and fragmented. [14] Need for this review Understanding purchasing processes can help us uncover why some of these inefficiencies and tensions exist, by exploring the inner workings of the environment, protocols, behaviours and organization of purchasing staff and departments, and thereby identifying areas for improved practices.…”
Section: Introduction Contextmentioning
confidence: 99%
See 1 more Smart Citation